Big data and dynamic capabilities: a bibliometric analysis and systematic literature review. Issue 8 (12th September 2019) - Rialti, Riccardo; Marzi, Giacomo; Ciappei, Cristiano; Busso, Donatella
Abstract : Purpose: Recently, several manuscripts about the effects of big data on organizations used dynamic capabilities as their main theoretical approach. However, these manuscripts still lack systematization. Consequently, the purpose of this paper is to systematize the literature on big data and dynamic capabilities. Design/methodology/approach: A bibliometric analysis was performed on 170 manuscripts extracted from the Clarivate Analytics Web of Science Core Collection database. The bibliometric analysis was integrated with a literature review. Findings: The bibliometric analysis revealed four clusters of papers on big data and dynamic capabilities: big data and supply chain management, knowledge management, decision making, business process management and big data analytics. The systematic literature review helped to clarify each clusters' content. Originality/value: To the authors' best knowledge, minimal attention has been paid to systematizing the literature on big data and dynamic capabilities.